2005
DOI: 10.1080/02652030500158617
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multicomponent method forFusariumtoxins using LC-MS/MS and its application during a survey for the content of T-2 toxin and deoxynivalenol in various feed and food samples

Abstract: A reliable, sensitive and selective method was developed to determine different Fusarium mycotoxins (trichothecenes Type A and B, zearalenone) simultaneously in cereals and cereal-based samples using liquid chromatography with tandem mass spectrometry (LC-ESI-MS/MS). Sample preparation is based on a standard solvent extraction step followed by two different kinds of solid-phase clean-up procedures: using a multifunctional MycoSep Õ material for trichothecenes and zearalenone. The average recoveries for trichot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 19 publications
6
69
1
Order By: Relevance
“…13) They showed that DON contamination was high (maximum level = 2350 ng/g), but the concentration of T-2 was lower than that in our study (maximum level = 0.95 ng/g). Schollenberger et al 18) showed that NIV, DON, HT-2, T-2 and ZEN occurred in foodstuffs marketed in Germany with DON the most commonly observed.…”
Section: Analysis Of Trs and Zen In Biscuits Based On Wheatmentioning
confidence: 69%
See 1 more Smart Citation
“…13) They showed that DON contamination was high (maximum level = 2350 ng/g), but the concentration of T-2 was lower than that in our study (maximum level = 0.95 ng/g). Schollenberger et al 18) showed that NIV, DON, HT-2, T-2 and ZEN occurred in foodstuffs marketed in Germany with DON the most commonly observed.…”
Section: Analysis Of Trs and Zen In Biscuits Based On Wheatmentioning
confidence: 69%
“…5,6) Co-contamination of Fusarium mycotoxins (TRs and ZEN) occurs worldwide in agricultural commodities and consumption of these has caused several outbreaks of intoxication in human and animal populations. [7][8][9][10][11][12] With the development of highly sensitive and simultaneous analytical methods, many reports regarding the co-contamination of Fusarium mycotoxins in processed cereal foods have been reported in Europe and North America, [13][14][15] but relatively little work is available for Asian countries despite these depending heavily on imported wheat and wheat-derived products. Thus, an accurate determination of processed food contaminated with these toxins is an urgent need for C 2010 The Pharmaceutical Society of Japan food supply.…”
Section: Iintroductionmentioning
confidence: 99%
“…Aflatoxins were separated in a UPLC instrument equipped with a matching UPLC Quaternary Solvent Manager, UPLC Sample Manager, UPLC Fluorescent Detector, and a C18 2.1 mm × 50 mm, 1.7 m column. Aflatoxin identity was determined by obtaining their UV and mass-spectral data and comparing them with published data [34]. Aflatoxin concentrations in samples were determined by reference to peak areas of commercial standards.…”
Section: Seed Inoculations and Aflatoxin Analysismentioning
confidence: 99%
“…C 8 , C 18 ), strong cation or anion exchangers (SCX, SAX) or polymeric materials with combined properties. Modern clean-up procedures employ multifunctional MycoSep Õ (Krska 1998;Radová et al 1998;Biselli and Hummert 2005;Ren et al 2007) or immunoaffinity columns (IAC) (Krska 1998), although these methods are more expensive than conventional clean-up methodologies. MycoSep Õ columns contain a mixture of charcoal, ion-exchange resins and other materials and are suitable for aflatoxins, trichothecenes, ochratoxins, zearalenone, moniliformin and patulin (Romerlabs 2007).…”
Section: Sample Preparation and Clean-upmentioning
confidence: 99%